2016
DOI: 10.2183/pjab.92.237
|View full text |Cite
|
Sign up to set email alerts
|

Microglial phospholipase D4 deficiency influences myelination during brain development

Abstract: Phospholipase D4 (PLD4) is expressed in activated microglia that transiently appear in white matter during postnatal brain development. Previous knockdown experiments using cultured microglia showed PLD4 involvement in phagocytosis and proliferation. To elucidate the role of PLD4 in vivo, PLD4-deficient mice were generated and the cerebella were examined at postnatal day 5 (P5) and P7, when PLD4 expression is highest in microglia. Wild type microglia showed strong immunoreactivity for microglial marker CD68 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…As depicted in the volcano plot (Fig. 5 ), in the CUD group, we found reduced levels in the following proteins: casein kinase 2 subunit alpha serine-threonine kinase, involved in controlling synapse organization and stability by regulation of NMDA subunits 49 ; ADP Ribosylation Factor 5 (ARF5), an activator of phospholipase D 50 , which is critically involved in myelin development 51 ; and Metabolism of Cobalamin Associated B (MMAB) that catalyzes vitamin B12 52 , which is known to have a key role in myelin repair and maintenance 53 . In addition, among the proteins with higher expression in CUD are serine and arginine rich splicing factor 3 (SRSF3), involved in regulating innate immune responses in activated microglia 54 ; Lumican (LUM), which has an important role in innate immunity 55 ; and Myotubularin-related protein 2 (MTMR2), a protein involved in membrane trafficking via dephosphorylation of phosphoinositides, such as PI(3)P. The mass spectrometry proteomics data have been deposited to the ProteomeXchange Consortium via the PRIDE partner repository with the data set identifier PXD025269.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…As depicted in the volcano plot (Fig. 5 ), in the CUD group, we found reduced levels in the following proteins: casein kinase 2 subunit alpha serine-threonine kinase, involved in controlling synapse organization and stability by regulation of NMDA subunits 49 ; ADP Ribosylation Factor 5 (ARF5), an activator of phospholipase D 50 , which is critically involved in myelin development 51 ; and Metabolism of Cobalamin Associated B (MMAB) that catalyzes vitamin B12 52 , which is known to have a key role in myelin repair and maintenance 53 . In addition, among the proteins with higher expression in CUD are serine and arginine rich splicing factor 3 (SRSF3), involved in regulating innate immune responses in activated microglia 54 ; Lumican (LUM), which has an important role in innate immunity 55 ; and Myotubularin-related protein 2 (MTMR2), a protein involved in membrane trafficking via dephosphorylation of phosphoinositides, such as PI(3)P. The mass spectrometry proteomics data have been deposited to the ProteomeXchange Consortium via the PRIDE partner repository with the data set identifier PXD025269.…”
Section: Resultsmentioning
confidence: 80%
“…Interestingly, we found significantly decreased levels of ARF5 (i.e., an activator of phospholipase D) 50 . Specifically, phospholipase D4 has an important role in the mechanisms of myelin development 51 . Furthermore, ARF5 was identified as part of the myelin proteome in the central and peripheral nervous systems 72 , 73 , suggesting that low ARF5 levels have implications for WM integrity.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that myelination of the mouse cerebellum is beginning around P5 to P8 (Chiba et al, 2016; Groteklaes, Bönisch, Eiberger, Christ, & Schilling, 2020). To analyze preference of myelination at the early-stage of cerebellar myelination, RV-GFP was injected into the white matter of P8 mouse cerebellum, and the mice were sacrificed at P12 to identify the axonal subtypes myelinated by the labeled oligodendrocytes with IHC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Miron et al (2013) have shown that microglia activated with interleukin (IL)‐13 or IL‐10 enhance survival and differentiation effects on OPCs. Activated (amoeboid) microglia in the white matter of postnatal developing brain express phospholipase D4, whose deficiency leads to myelination delay in cerebellum, and corpus callosum (Chiba et al, 2016). In vitro studies with microglia‐oligodendrocyte co‐culture showed that microglia stimulated the synthesis of sulfatide, a myelin specific galactolipid and also increased the expression of MBP and PLP in oligodendrocytes suggesting that these cells play a role in myelination (Hamilton and Rome, 1994).…”
Section: Role Of Microglia In Myelinationmentioning
confidence: 99%
“…Transformation of OPCs into pre‐myelinating oligodendrocytes and eventually into mature myelin‐producing oligodendrocytes, sets the beginning of axonal myelination (Pfeiffer et al, 1993). In addition to oligodendrocytes, other glial cells like astrocytes and microglia also secrete multiple factors that affect the myelination process in the developing brain (Lundgaard et al, 2014; Nash et al, 2011; Stankoff et al, 2002; Xiao et al, 2010; Chiba et al, 2016). Various growth factors, protein kinases and extracellular matrix molecules are involved in modulating the process of myelination (Bauer et al, 2009; Bercury and Macklin, 2015).…”
Section: Introductionmentioning
confidence: 99%